Card & James' Business Law for Business, Accounting & Finance Students - Roach, Lee (College teacher); Card, Richard; Ghandhi, Jennifer, 1949- (Oxford : Oxford University Press, 2012)
This text provides a rigorous analysis of business law for students taking business and finance related courses.
Previous ed.: 2009.
Includes bibliographical references and index.
Keywords: Business law -- England; Business law -- Wales; Law